1997
DOI: 10.1063/1.473961
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations of the polarizability and the hyperpolarizability of C60

Abstract: The linear polarizability, α, and the second hyperpolarizability, γ, of C60 in gas phase have been computed by ab initio cubic response theory in the random phase approximation and with an efficient parallel implementation. With a tailored, well-tested, basis set, containing more than 1000 contracted basis functions the average values of α and γ are predicted to be 8.58×10−23 cm3 and 5.73×10−35 esu, respectively, which are about 8 and 9 times larger than the corresponding values for benzene calculated at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…Conversely, their polarizabilities (a) are substantially different: an HF/3-21G calculation yields average volume polarizabilities of a 88 and 24 ä 3 for 1 and 2, respectively (the value for 1 compares favorably with the value for C 60 itself, a 86 ä 3 ). [19] The polarizability of water (1.45 ä 3 ) is also substantially smaller than that of 1-octanol (17 ä 3 , estimated from that of di-nbutyl ether [20] ). From the classical expression for the dispersive interaction of two spherical particles with given a and ionization potential I, [Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, their polarizabilities (a) are substantially different: an HF/3-21G calculation yields average volume polarizabilities of a 88 and 24 ä 3 for 1 and 2, respectively (the value for 1 compares favorably with the value for C 60 itself, a 86 ä 3 ). [19] The polarizability of water (1.45 ä 3 ) is also substantially smaller than that of 1-octanol (17 ä 3 , estimated from that of di-nbutyl ether [20] ). From the classical expression for the dispersive interaction of two spherical particles with given a and ionization potential I, [Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a large scatter in both the experimental and theoretical results, there seems to be a growing consensus on both the theoretical 5,17 and experimental 16,18 sides that the hyperpolarizability of C 60 is much smaller than initially thought.…”
Section: Introductionmentioning
confidence: 99%
“…Also presented in Table 3 are three recent theoretical predictions of the second hyperpolarizablility of C 60 . A comparison with experiments are difficult due to the large differences in the experimental results [5][6][7] and the comparison will therefore only be made with theoretical results. In this work we have neglected vibrational, dispersion and solvent effect and these factors have to be considered when comparing with experiments.…”
Section: Second Hyperpolarizability Of C 60mentioning
confidence: 99%
“…Recently both experiments [3,4] and theory [5][6][7] have shown that the third-order nonlinearity of C 60 is smaller than first assumed. For this reason the third-order nonlinearity of derivatives of C 60 have been experimentally investigated and found to provide a large increase in the nonlinearity compared with the pure C 60 , see e.g.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation